Effects of Losartan versus Enalapril on Serum Uric Acid Levels in Hypertensive Patients with Metabolic Syndrome - A. A. Al-Thanoon, Zeina; H. Mahmood, Isam (Iraqi Journal of Pharmaceutical Sciences, 2017)
To investigate the effects of losartan and enalapril on serum uric acid in hypertensive patients with metabolic syndrome, one hundred and twenty six newly diagnosed mild hypertensive patients, having markers of metabolic syndrome included in the study. The patients were divided into two groups. Group 1 (60 patients) was given losartan (50 mg/ day) and group 2 (66 patients) enalapril (20 mg/ day) for a duration of 2 months. A control group of seventy apparently healthy individuals were included. Metabolic syndrome was diagnosed according to diagnostic criteria of metabolic syndrome related to the American National Cholesterol Education Program-Adult Treatment Panel III. Serum uric acid levels were measured before and after drug administration. The results revealed a significant higher levels of uric acid were found in the hypertensive patients as compared with control group and a significant drop of uric acid was noted after treatment with losartan but not with enalapril. In conclusions: this study demonstrates significantly higher serum uric acid concentrations in hypertensive patients having markers of metabolic syndrome. Losartan but not enalapril therapy produced a significant fall in the serum uric acid level. Losartan can be useful therapeutic agent to control blood pressure and to reduce serum uric acid level in hypertensive patients having markers of metabolic syndrome and hyperuricaemia.Key words: Hypertension, metabolic syndrome, uric acid, losartan, enalapril.